Regulation of photosynthesis through source: sink imbalance in citrus is mediated by carbohydrate content in leaves - Iglesias, Domingo J.; Lliso, Ignacio; Tadeo, Francisco R.; Talón, Manuel (2017)
In citrus, the occurrence of a sink effect on photosynthesis (A) is controversial. Leaf carbohydrates and photosynthetic rates in field-grown trees of Satsuma mandarin (Citrus unshiu [Mak.] Marc.) cv. Okitsu, were measured to elucidate whether or not the demand for photoassimilates regulates A. The data indicated that the source-sink imbalances induced by different treatments altered both soluble (sucrose, glucose and fructose) and insoluble carbohydrates in leaves, as well as photosynthetic rates. In general, girdling and defruiting increased starch and reduced photosynthesis, whereas source-limiting conditions imposed through partial defoliations had the opposite effect. These results are compatible with the assumption that a lack of sink activity leads to carbohydrate accumulation and feedback inhibition of A, and vice versa. Further evidence supporting a source-sink effect on A was provided by measurements of the dry matter: leaf area ratio, since defoliations, for example, increased this ratio. The in vivo sucrose supplementation to plants with different source: sink ratios (control, defoliated, girdled and defruited plants) increased carbohydrates and reduced photosynthesis. This suggests that sugars may have, per se, the potential to repress photosynthetic rates in intact plants with active sinks. Based on these results we propose that sugar accumulation in citrus leaves causes a feedback inhibition of A.